The results of durum wheat breeding in Russia for carotenoid pigments content in kernels - M. G. Myasnikova; P. N. Malchikov; E. N. Shabolkina; N. V. Anisimkina; M. A. Rozova; T. V. Chakheeva (Зерновое хозяйство России, 2020)
The concentration of carotenoid pigments in durum wheat kernels determines up to 30.0% of the quality of the final product.  The purpose of the current study is to analyze the results of breeding improvement of spring durum wheat according to this trait in  Russia, at all breeding stages. There was conducted the study based on the varieties of 4–7 stages of breeding in 11 environmental  complexes (year, point) in 2014–2018. There were studied 29 genotypes. The plot area was 5.0–10.0 m2 with a 3-fold repetition.  The concentration of yellow pigments in kernels was identified by extracting them with saturated n-butanol and with a subsequent  photo-colorimetry at a wavelength of 440 ... 450 nm. As a result, there was established a significant increase in the concentration of  carotenoids in kernels of the best genotypes in the main breeding Russian centers (+25–70.0% to the variety of 4-th stage of breeding  “Kharkovsky 46”). The best varieties were “Bezenchukskaya zolotistaya”, “Bezenchukskaya krepost”, “Bezenchukskaya 210” (Samara  RIA), “Saratovskaya zolotistaya” (RIA of the South-East) and the breeding lines “Gordeiforme 677” (FGBNU FANTSA), “D2098”  (RIA of the South-East) and “1368D-18” (Samara RIA). These genotypes are recommended to be used as initial material in breeding  and for the development of recombinant inbred lines for marking QTL that control the synthesis of carotenoids in durum wheat kernels  and organize a marker-associated breeding technology on this basis.